Allelopathic Potential of Winter Wheat Varieties for Weed Suppression - C. Bott; A. Dille; A. Mohammad; L. Simão; L. O. Pradella; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2023)
Summer weeds are an expensive economic and environmental problem during the fallow period following the harvest of a wheat crop. Anecdotal evidence suggests that different wheat varieties impact the need for weed control in the subsequent fallow period differently, with reasons ranging from residue amount and quality to the allelopathic potential of such residue. Thus, our objectives were to compare the allelopathic effects of different winter wheat varieties on weed and crop germination suppression. We collected the residue left after harvest of 25 varieties grown in a randomized complete block design in two Kansas locations (Hays and Great Bend) during 2022. The residue of the different varieties were combined (replications within location), dried, ground, and used to create extracts with 5% concentration that were later used in a growth chamber study. total of 50 seeds for weed species Palmer amaranth (Amaranthus palmeri) and giant foxtail (Setaria faberi), and 25 seeds for grain sorghum (Sorghum bicolor), were added to petri dishes in combination with 5 mL of each extract in four replicates. Petri dishes were sealed with Parafilm and placed in a dark growth chamber set to 84/75°F day/night temperatures. Seed germination was counted after 5 days. There were significant location by variety interactions in the control of both weed species, with greater weed control resulting from the residue derived from Great Bend (6–100% control) than from Hays (-10 to 69%). The difference among varieties was also large, and depending on weed species and location, ranged from as little as 26% to as much as 90% (these differences reflected contrasts between the varieties with minimum versus those with maximum control). All wheat varieties significantly reduced seed germination of Palmer amaranth and giant foxtail, but varieties differed in their germination suppression potential. The allelopathic effects of wheat varieties could be additional targets of breeding programs for reduced weed pressure. Meanwhile, grain sorghum germination was minimally impacted by allelopathic effects of wheat residue.
Keywords: wheat varieties; allelopathy; wheat residue; weed control